A potential endodontic misdiagnosis: periapical central giant cell granuloma - Cahyareni, Firlana; Hanafi, Eva Yulianti; Romdlon, Mahindra Awwaludin; Fauziyah, Erlina; Gustianto, Yudhy; Pramanik, Farina; Sam, Belly; Muryani, Anna (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2025)
Objectives: The purpose of this case study was to report a periapical central giant cell granuloma post-endodontic treatment. Case Report: A 32-year-old female patient presented to the Dental Radiology Unit of Dental Hospital Universitas Padjadjaran with a CBCT referral letter, diagnosed clinically with periapical abscess of tooth 22 post-endodontic treatment. The patient had a history of coming to the emergency room with a fair general condition and complained of pain and swelling of the left upper lip. The CBCT result demonstrated a large radiolucent lesion at the periapical of tooth 22 with a well-defined border that extended to the apical area of tooth 21. There was a cortical destruction on the palatal and labial alveolar bone. Density analysis revealed an average density of 145.2 Grayscale. Conclusion: Lesions might be analysed using both qualitative and quantitative methods with CBCT 3D. These methods lead to the suspicion of periapical central giant cell granuloma in this case's lesion. Keywords: Periapical central giant cell granuloma, endodontic lesion, CBCT 3D